Analysis of Factors that Form the Surplus of Last Year's Budget Calculation (SiLPA) In the Mataram City Regional Budget for the 2012 - 2022 Period - Janna, Ilza Lail Fatul; Yasin, Muaidy; Sujadi, Sujadi (Eastasouth Institute, 2024)
This study is entitled